Socioeconomic Inequalities Increase the Probability of Ketoacidosis at Diagnosis of Type 1 Diabetes: A 2014–2016 Nationwide Study of 2,679 Italian Children - Gesuita, Rosaria; Maffeis, Claudio; Bonfanti, Riccardo; Cardella, Francesca; Citriniti, Felice; D'Annunzio, Giuseppe; Franzese, Adriana; Iafusco, Dario; Iannilli, Antonio; Lombardo, Fortunato; Maltoni, Giulio; Patera, Ippolita Patrizia; et al. (Frontiers in Pediatrics, 2020)
This study aims to compare the frequency of Diabetic Ketoacidosis (DKA) at diagnosis in 2014–2016 with the one previously reported in 2004–2013; and to assess the association between family socioeconomic status and DKA at type 1 diabetes (T1D) diagnosis in children <15 years of age from 2014 to 2016. Methods: This nationwide, population-based, observational study included 2,679 children diagnosed with T1D from 54 Italian centers for pediatric diabetes during 2014–2016. The ISPAD criteria for DKA were used as a standard reference. The overall and by age frequency of DKA between the two time periods were compared. The association between family socioeconomic status and DKA was assessed using multiple logistic regression analysis. Results: Nine hundred and eighty nine children had DKA (36.9, 95% CI: 35.1–38.8). The frequency of DKA was significantly lower in 2014–2016 in comparison to 2004–2013 (40.3, 95% CI: 39.3–41.4, p = 0.002). The probability of having DKA at diagnosis was lower in mothers with a high level of education (OR = 0.69, 95% CI: 0.51–0.93) or a high level of occupation (OR = 0.76, 95% CI: 0.58 0.99), and in fathers with a high level of occupation (OR = 0.72, 95% CI: 0.55–0.94). Children living in Southern Italy had a higher probability of diagnosis with severe DKA than children living in Central Italy. Conclusion: There was a decrease in the frequency of DKA in children diagnosed with T1D under 15 years of age during 2014–2016. However, DKA frequency remains unacceptably high. This study demonstrated that socioeconomic inequalities, measured as low education and occupational levels, were associated with an increased probability of DKA at T1D diagnosis.